(untitled) (Per Musi, 2018)
Guitarists are susceptible to multiple injuries directly related to faulty left-hand technique: carpal tunnel syndrome, lateral epicondylitis, median epicondylitis, neuropathy of the ulnar nerve, supinator syndrome, osteoarthritis and capsulitis of the first carpometacarpal and digital neuritis. A literature review shows that the causes of these injuries are all related to excessive flexion or extension of the wrist, exaggerated bending of the elbow, prolonged periods of maximal supination of the wrist and large amounts of tensioned positions. The article analyzes guitar left-hand technique and proposes technical and postural approaches that address these causes and theoretically decrease the risk of playing-related injuries.